The Iliofemoral tortuosity score predicts access and bleeding complications during transfemoral transcatheter aortic valve replacement: Data from the VIenna Cardio Thoracic aOrtic valve registrY (VICTORY). (2nd February 2021) - Mach, Markus; Poschner, Thomas; Hasan, Waseem; Szalkiewicz, Philipp; Andreas, Martin; Winkler, Bernhard; Geisler, Stephanie; Geisler, Daniela; Rudziński, Piotr N.; Watzal, Victoria; Strouhal, Andreas; Adlbrecht, Christopher; et al.
Abstract: Background: Arterial tortuosity is linked to a higher risk of adverse clinical events after transfemoral transcatheter aortic valve replacement (TF‐TAVR). Currently, there are no assessment tools that can quantify this variable in three‐dimensional space. This study investigated the impact of novel scoring methods of iliofemoral tortuosity on access and bleeding complications after TF‐TAVR. Methods: The main access vessel was assessed between the aortoiliacal and femoral bifurcation in preoperative multislice computed tomography scans of 240 consecutive patients undergoing TF‐TAVR. Tortuosity was assessed by three methods: largest single angle, sum of all angles, and iliofemoral tortuosity (IFT) score [((true vessel length/ideal vessel length)‐1)*100]. The primary study endpoint was a composite of access and bleeding complications. The secondary study endpoints were 30‐day mortality and long‐term survival. Results: Among 240 patients, only the IFT score demonstrated a good positive correlation with the composite primary endpoint of access and bleeding complications ( P = 0.031). A higher incidence of access and bleeding complications was found in patients with a higher IFT score (56 [36.8%] vs 17 [19.3%]; P = 0.003). In a multivariate logistic regression analysis, only the IFT score was a significant predictor of the primary endpoint (OR: 2.11; 95% CI: 1.09‐4.05; P = 0.026). Conclusion: Vascular tortuosity is an underestimated risk factor during TF‐TAVR. The IFT score is a valuable tool in risk stratification before TF‐TAVR, predicting periprocedural access and bleeding complications.